JOŽICA ČEH STEGER: EKOKRITIKA IN LITERARNE UPODOBITVE NARAVE: Maribor: Založba Litera, 2015. 349 str. - Vičar, Branislava (Slavia Centralis, 2020)
The author presents the monograph by Jožica Čeh Steger Ecocriticism and Literary Representations of Nature (2015).
Keywords: Jožica Čeh Steger; ecocriticism; review; representation of nature; ecosemiotic research